2016
DOI: 10.1371/journal.pone.0158970
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Validation of SNP Markers Linked to Dwarf Traits Using SLAF-Seq Technology in Lagerstroemia

Abstract: The genetic control of plant architecture is a promising approach to breed desirable cultivars, particularly in ornamental flowers. In this study, the F1 population (142 seedlings) derived from Lagerstroemia fauriei (non-dwarf) × L. indica ‘Pocomoke’ (dwarf) was phenotyped for six traits (plant height (PH), internode length (IL), internode number, primary lateral branch height (PLBH), secondary lateral branch height and primary branch number), and the IL and PLBH traits were positively correlated with the PH t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 66 publications
0
16
0
Order By: Relevance
“…Research on the plant architecture of crape myrtle is mainly focused on dwarf traits. Two markers that are highly correlated with internode length and one marker that is highly correlated with primary lateral branch height have been validated in crape myrtle 34 . The analysis of transcriptome and hormone levels in dwarf and non-dwarf crape myrtles suggested that internode length is controlled by an interaction between auxin and GA4 32 .…”
Section: Introductionmentioning
confidence: 99%
“…Research on the plant architecture of crape myrtle is mainly focused on dwarf traits. Two markers that are highly correlated with internode length and one marker that is highly correlated with primary lateral branch height have been validated in crape myrtle 34 . The analysis of transcriptome and hormone levels in dwarf and non-dwarf crape myrtles suggested that internode length is controlled by an interaction between auxin and GA4 32 .…”
Section: Introductionmentioning
confidence: 99%
“…To test the amplification efficiency of the selected EST-SSRs, the F1 segregating population was employed in this study (Ye et al, 2016). Seven Lagerstroemia species were used to confirm the cross-species transferability of selected EST-SSR markers, including L. indica, L. fauriei, L. speciosa, L. excelsa, L. caudata, L. limii and L. subcostata.…”
Section: Plant Materials and Dna Extractionmentioning
confidence: 99%
“…And then a set of 30 primer pairs were selected according to their polymorphism and identification ability, in order to analyze the genetic diversity among 73 accessions, and transferability across seven Lagerstroemia species. The PCR amplification conditions and procedures were referenced from Ye et al (2016). For analysis of genetic relationship, the forward primers of SSRs were elongated from M13 universal sequences appended to the 5'-end (Schuelke, 2000).…”
Section: Development Of Est-ssr Markersmentioning
confidence: 99%
See 1 more Smart Citation
“…In our previous studies, the F1 population was used to investigate the genetic inheritance of plant architecture traits (Ye et al, 2015(Ye et al, , 2016. Herein, we performed the transcriptome analysis for the parents in order to screen the target genes, as well as the massive EST-SSR markers.…”
Section: Ssr Detection and Primer Designmentioning
confidence: 99%